SOME BIOLOGICAL AND ECOLOGICAL STUDIES ON POPLAR BUD PSYLLID Egeirotrioza justa BURK & LAUTE IN MOSUL REGION - Ismail N. Almaroof (Mesopotamia Journal of Agriculture)
This study was conducted on poplar bud psyllid in Ninevah during the years 2004 and 2005. For the first time Egeirotrioza justa Burk & Laute has been studied and recorded in Iraq. The poplar bud psyllid Egeirotrioza justa Burck & Laute attacks Populous euphratica trees and as a result of feeding by newly nymphs, small galls are formed on the twig tissues near the buds. The adults appeared on the trees during May to July. Mating usually occurred during the first week of May, mean periods of pre – oviposition, oviposition and post – oviposition (1.8 ± 0.74, 5.30 ± 0.57,and 2.00 ± 0.49) days, respectively. Egg laying took place singly on the leaf petiols, and on bouth services and margins of mature as well as the tender young leaves and twigs. The average number of eggs laid per female was 21.80, hatching of eggs was 80%, and sex ratio was 1:2. This species hibernates as a second nymphal instar. This insect has one generation per year.The study indicated that the south direction of a tree from south side of the forest and at a height more than 3m for trees were represented high average number of eggs nymphs and adults (100.00, 64.48,and 57.40), respectively.